What is the effect of sensori-motor training on functional outcome and balance performance of patients' undergoing TKR? A systematic review. Issue 2 (June 2016) - Moutzouri, M.; Gleeson, N.; Billis, E.; Panoutsopoulou, I.; Gliatis, J.
Abstract: Objectives: Total knee replacement (TKR) has a beneficial effect on patients' functional ability; however, incidence of falls and deficits on proprioception are not restored even 1-year after surgery. Early and intensive exercise post-TKR has received limited endorsement in the literature. The aim of this review was to systemically identify and critically appraise clinical studies investigating the effect of sensori-motor training on functional and balance performance in TKR patients. Data sources: The electronic databases Cochrane Library, MEDLINE, EMBASE, CINAHL, PEDro and the register of current controlled trials were searched up to September 2014. Review methods: Two independent reviewers used predefined inclusion and exclusion criteria to identify all eligible articles. Eligible articles were summarized and critically reviewed, using the PEDro scale. Results: Two hundred and seventy six articles were screened, six were included. The studies, presented the results of 409 patients (269 intervention, 140 control). A range of rehabilitation protocols were defined by components of proprioception, postural control, balance perturbation and coordination. All studies supported the use of sensori-motor training as an additional element in patients' rehabilitation protocols. Clinical performance-based tests (more than relevant patient-reported measures) showed that functional ability and balance were improved compared to controls. The robustness of evidence was compromised because most of the studies were underpowered. Conclusions: Limited robust (Ia) evidence supports the equal effectiveness of functional rehabilitation program as a functional rehabilitation enhanced with sensori-motor elements in patients post-TKR. However, dose-response parameters of exercise eliciting improvement warrant further investigation.